Thinking Conditioning through Practice - Langsdorf, Heike; Arteaga, Alex (Gent : Art Paper Editions, 2018)
Contributors: Alex Arteaga, Julia Barrios de la Mora, Julien Bruneau, Laetitia Gendr , Miram Rohde, Heike Langsdorf, Kristof Van Baarle
boek